EFFECTIVENESS OF STEM CELL THERAPY IN MYOCARDIAL INFARCTION BASED ON ENZYME ACTIVITY AND LIVER HISTOPATOLOGY - Rahmi, Riska Asria Sa'adatur; Gunanti, Gunanti; Noviana, Deni; Harlina, Eva (Universitas Syiah Kuala, 2024)
This research aims to study the effectiveness of single placenta stem cell therapy (ST) or a combination of cardiomyocyte co-cultures in pigs with myocardial infarction based on enzymes alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activity as well as liver histopathology. Nine pigs were divided into three treatment groups (K1, K2, and K3) consisting of three pigs per group. Blood sampling was performed one-hour pre-surgery, post-ST-elevation, and eight weeks post-therapy. The experimental animals were treated for eight weeks, then euthanized and necropsied for liver removal. ALT and AST values were analyzed using one-way analysis of variance (ANOVA) and followed by Tukey's test. Histopathological changes in liver tissue were analyzed using Image J 1.53 software, and the measured data were analyzed using oneway ANOVA. The results showed an increase in the ALT and AST values of the three treatment groups on post-ST-elevation blood sampling but were still within normal limits except for K1. ALT and AST values decreased significantly (P0.05) in the group treated with single placental stem cell (K2) or combined cardiomyocyte co-culture (K3). The ALT value of K3 decreased but not significantly (P0.05) compared to K2. The AST value of K3 decreased significantly (P0.05) but was not significantly different (P0.05) compared to K2. The liver tissue showed circulatory disturbances in the central venous congestion, portal vein, sinusoidal dilatation and congestion, and hepatocyte changes in the form of centrilobular necrosis and hydropic degeneration. Stem cell therapy alone (K2) or in combination with cardiomyocyte co-culture (K3) had similar percentage of centrilobular necrosis which was significantly lower than K1 (P0.05). Hepatocyte hydropic degeneration on K2 was classified as mild, whereas on K3 was classified as moderate. As conclusion, administration of placental stem cell therapy alone or in combination with cardiomyocyte co-culture can reduce ALT and AST values and could repair liver tissue.